Transport of soil-aged silver nanoparticles in unsaturated sand - Kumahor, Samuel; Hron, Pavel; Metreveli, George; Schaumann, Gabriele E.; Klitzke, Sondra; Lang, Friederike; Vogel, Hans-Jörg (Journal of contaminant hydrology, 2016)
Engineered nanoparticles released into soils may be coated with humic substances, potentially modifying their surface properties. Due to their amphiphilic nature, humic coating is expected to affect interaction of nanoparticle at the air-water interface. In this study, we explored the roles of the air-water interface and solid-water interface as potential sites for nanoparticle attachment and the importance of hydrophobic interactions for nanoparticle attachment at the air-water interface. By exposing Ag nanoparticles to soil solution extracted from the upper soil horizon of a floodplain soil, the mobility of the resulting “soil-aged” Ag nanoparticles was investigated and compared with the mobility of citrate-coated Ag nanoparticles as investigated in an earlier study. The mobility was determined as a function of hydrologic conditions and solution chemistry using column breakthrough curves and numerical modeling. Specifically, we compared the mobility of both types of nanoparticles for different unsaturated flow conditions and for pH=5 and pH=9. The soil-aged Ag NP were less mobile at pH=5 than at pH=9 due to lower electrostatic repulsion at pH=5 for both types of interfaces. Moreover, the physical flow field at different water contents modified the impact of chemical forces at the solid-water interface. An extended Derjaguin-Landau-Verwey-Overbeek (eDLVO) model did not provide satisfactory explanation of the observed transport phenomena unlike for the citrate-coated case. For instance, the eDLVO model assuming sphere-plate geometry predicts a high energy barrier (>90 kT) for the solid-water interface, indicating that nanoparticle attachment is less likely. Furthermore, retardation through reversible sorption at the air-water interface was probably less relevant for soil-aged nanoparticles than for citrate-coated nanoparticles. An additional cation bridging mechanism and straining within the flow field may have enhanced nanoparticle retention at the solid-water interface. The results indicate that the mobility of engineered Ag nanoparticles is sensitive to solution chemistry, especially pH and the concentration of multivalent cations, and to the unsaturated flow conditions influencing particle interaction at biogeochemical interfaces.
Gesehen am 04.06.2020